Functional Properties of the MAP Kinase UeKpp2 in Ustilago esculenta - Zhang, Yafen; Hu, Yingli; Cao, Qianchao; Yin, Yumei; Xia, Wenqiang; Cui, Haifeng; Yu, Xiaoping; Ye, Zihong (Frontiers in Microbiology, 2020)
Ustilago esculenta undergoes an endophytic life cycle in Zizania latifolia. It induces the stem of its host to swell, forming the edible galls called jiaobai in China, which are the second most commonly cultivated aquatic vegetable in China. Z. latifolia raised for jiaobai can only reproduce asexually because the U. esculenta infection completely inhibits flowering. The infection and proliferation in the host plants during the formation of edible gall differ from those of conventional pathogens. Previous studies have shown a close relationship between mitogen-activated protein kinase (MAPK) and fungal pathogenesis. In this study, we explored the functional properties of the MAPK UeKpp2. Cross-species complementation assays were carried out, which indicated a functional complementation between the UeKpp2 of U. esculanta and the Kpp2 of U. maydis. Next, UeKpp2 mutants of the UeT14 and the UeT55 sporidia background were generated; these showed an aberrant morphology of budding cells, and attenuated mating and filamentous growth in vitro, in the context of normal pathogenicity. Interestingly, we identified another protein kinase, UeUkc1, which acted downstream of UeKpp2 and may participate in the regulation of cell shape. We also found a defect of filamentous growth in UeKpp2 mutants that was not related to a defect of the induction of mating-type genes but was directly related to a defect in UeRbf1 induction. Overall, our results indicate an important role for UeKpp2 in U. esculenta that is slightly different from those reported for other smut fungi.